Genetic strategies for enhancing litter size and birth weight uniformity in piglets - Boonkum, Wuttigrai; Permthongchoochai, Suwanee; Chankitisakul, Vibuntita; Duangjinda, Monchai (Frontiers in Veterinary Science, 2025)
This study aimed to estimate the genetic parameters and develop selection indices for litter size and birth weight uniformity in piglets. These traits are crucial for improving productivity and profitability of swine production. Data were collected from 9,969 litters of 4,465 sows and 106,463 piglets of various breeds from a farm in Thailand. The analyzed traits included the total number born (TNB), number born alive (NBA), litter birth weight (LBW), mean birth weight, and individual birth weight. The assessed piglet uniformity traits included the difference between the maximum and minimum values (range), interquartile range of birth weight (IQRBW), variance in birth weight (VBW), standard deviation of birth weight (SDBW), and coefficient of variation of birth weight (CVBW). Variance components and genetic parameters were estimated using a multiple-trait animal model and the average information-restricted maximum likelihood method. The appropriate selection index (I) was determined based on heritability, genetic correlations between traits, and the economic significance of the traits. The results revealed that litter size traits (TNB and NBA) and piglet birth weight uniformity traits (Range, IQRBW, VBW, SDBW, and CVBW) exhibited low heritability (p < 0.1), suggesting that environmental factors have a substantial influence. In contrast, birth weight traits showed moderate heritability (approximately 0.2). Negative genetic correlations between litter size and birth weight traits were observed, indicating that increasing litter size might reduce piglet birth weight and uniformity, potentially affecting survival rate. A selection index combining NBA, LBW, and CVBW was constructed to optimize the selection process for productivity and uniformity. In conclusion, genetic improvement programs should prioritize litter size and birth weight uniformity to enhance productivity and uniformity on commercial pig farms. These findings can assist breeders in developing more effective selection strategies, ultimately resulting in larger, more uniform litters and improved overall farm efficiency.